Heterogeneous Transesterification Of Rubber Seed Oil Biodiesel Production - Mahanum, Mohd Zamberi; Farid Nasir, Ani; Mohd Fadzli, Abdollah (Penerbit UTM Press, 2016)
An experimental investigation was conducted to explore the effects of using waste cockle shells as a heterogeneous catalyst on the transesterification process of very high free fatty acid (FFA) rubber seeds oil with methanol. The waste cockle was calcined at 900oC for 4 hours and was employed as a source of calcium oxide (CaO). SEM, XRD and XRF were adopted to analyze the catalyst characterization. The process variables namely oil molar ratio, catalyst concentration and reaction time were optimized using response surface methodology (RSM) based on central composite design (CCD) method. The optimum yield of 88.06% was obtained for the final product of biodiesel with optimal conditions was obtained as: molar ratio of methanol to oil of around 15.57:1, 9 % catalyst weight percentage with 2.81 hours reaction time. All the fuel properties were analyzed according to the ASTM D6751 and EN-14214 standards in terms of viscosity, acid value, density and flash point.